Biologia de Chrysoperla externa (Hagen, 1861)(Neuroptera, Chrysopidae) alimentada com diferentes dietas - Ribeiro, Maria José (1988)
The objective of this work to study the biology of larvae and adults of Chrysoperla externa (Hagen, 1861) (Neuroptera, Chrysopidae) fed with different sources of food. The experiments were carried out in the Insect Biology Laboratory at "Escola Superior de Agricultura de Lavras", Minas Gerais State, Brazil. The temperature was maintained at 25 ± 2°C; the relative humidity was 70 ± 10% and 14:10 hours L:D photoperiod. Larvae fed with eggs of Alabama argillacea (Hueb.) developed best in comparison with other sources of food tested. The mortality among larvae fed with the Aphis gossypii (Glov) was a little higher. The mortality was very high among larvae fed with eggs of Spodoptera frugiperda (Smith), specially during the first and second instars. Larvae fed with the aphid Toxoptera citricidus Kirk. generally died before they reached the third instar. Biological aspects of adults, which were obtained from larvae fed with eggs of Anagasta kuehniella (Zeller), were examined for insects feeding on seven different diets, including polen, honey bee (40% in water) and mixtures of the following protein sources:'Proteina Texturizada de Soja" , "Sojinha" , "New Life"' and yeast. The greatest reproduction rate was observed for insects fed with a mixture of yeast, honey bee and water. Virgin females laid eggs that were not fertile and most of which did not have stalk. Mated females kept together with males laid a number of eggs significanty higher than those isolated after mating. The biology of adults obtained from larvae fed with eggs of A. kuehniella was compared with that of adults obtained from larvae fed with eggs of A. argillacea. It was observed that females from larvae fed with eggs of A. kuehniella had a shorter pré oviposition period, whereas those from larvae fed with eggs of A. argillacea had the periods of post oviposition and longevity reduced